Coliphages as indicators of primary wastewater treatment efficiency by constructed wetlands. (2nd March 2023) - Hernandez-Rivera, Gisela; Santiago-Rodriguez, Tasha M.; Toranzos, Gary A.
Abstract: Constructed wetlands are an efficient and cost-effective system for the treatment of wastewater that can be reused for diverse purposes, including irrigation; however, few studies have determined the efficiency of microbial removal by constructed wetlands in tropical regions. Therefore, the present study aimed to determine the microbial quality of the influent and effluent of a constructed wetland in Puerto Rico, using traditional bacterial indicators (i.e., thermotolerant coliforms and enterococci), as well as somatic and male-specific (F+) coliphages. Results showed that over 99.9 and 97.7% of thermotolerant coliforms and enterococci were removed after treatment by constructed wetlands, respectively. Notably, approximately 84.0% of male-specific (F+) coliphages were removed, while somatic and total coliphages exhibited differing removal percentages at different steps during treatment by constructed wetlands. The potential risk of the presence of enteric viruses in treated wastewater by constructed wetlands may increase when considering traditional bacterial indicators exclusively. The present study may aid in the efforts to determine public health concerns associated with the exposure of bioaerosols resulting from wastewater treatment by constructed wetlands. HIGHLIGHTS: Microbial removal efficiency by constructed wetlands in tropical regions remains largely unexplored. Coliphages were tested as indicators of microbial removal efficiency by a constructed wetland in Puerto Rico. Approximately 84.0% of male-specific (F+) coliphages were removed. The present study aids to determine the effectiveness of coliphages as indicators of wastewater treatment by constructed wetlands.